Sistem Informasi Peringatan Dini Pengendalian Hama dan Penyakit Tanaman Pangan Berbasis Mobile Computing - Harisno Harisno; Wandy Apriyadi; Yudiana Herman; Tono Tono (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Concerning the several pest attacks in Karawang, Cirebon, and Cianjur districts a mobile computing-based information system is built to accelerate the data flow and early warning information to the person in charge at Ministry of Agriculture. Based on interviews and surveys to the locations planted with rice, corn and soybeans some data of the breadth and intensity of pest attack is obtained, used as the basis design for the early warning data structure. The information systems development method refers to the systems development life cycle (SDLC): identification of needs data and information, analysis and system design, testing, implementation and evaluation system. The result is a mobile computing-based information system of pest control and crop disease early warning that can accelerate data and information transmission that the stakeholders in the Ministry of Agriculture can make decisions quickly and correctly.